2013
DOI: 10.1186/1472-6882-13-261
|View full text |Cite
|
Sign up to set email alerts
|

Neurite outgrowth stimulatory effects of culinary-medicinal mushrooms and their toxicity assessment using differentiating Neuro-2a and embryonic fibroblast BALB/3T3

Abstract: BackgroundMushrooms are not only regarded as gourmet cuisine but also as therapeutic agent to promote cognition health. However, little toxicological information is available regarding their safety. Therefore, the aim of this study was to screen selected ethno-pharmacologically important mushrooms for stimulatory effects on neurite outgrowth and to test for any cytotoxicity.MethodsThe stimulatory effect of mushrooms on neurite outgrowth was assessed in differentiating mouse neuroblastoma (N2a) cells. Neurite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 43 publications
1
42
0
2
Order By: Relevance
“…Consistent with our previous study, the sclerotia of L. rhinocerotis reported neurite outgrowth in N2a. 29 It was recently shown that sclerotial extract performs better than mycelial extract. 29 Advanced study shows maximum neurite extension for L. rhinocerotis and curcumin at 21.1% at 20 µg/mL and 29.47% at 10 µg/mL on PC-12 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our previous study, the sclerotia of L. rhinocerotis reported neurite outgrowth in N2a. 29 It was recently shown that sclerotial extract performs better than mycelial extract. 29 Advanced study shows maximum neurite extension for L. rhinocerotis and curcumin at 21.1% at 20 µg/mL and 29.47% at 10 µg/mL on PC-12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…29 It was recently shown that sclerotial extract performs better than mycelial extract. 29 Advanced study shows maximum neurite extension for L. rhinocerotis and curcumin at 21.1% at 20 µg/mL and 29.47% at 10 µg/mL on PC-12 cells. 30 Combining 20 µg/mL of L. rhinocerotis with 1 µg/ mL curcumin gave 27.2% neurite extension in PC12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hyde), formerly known as Panus/Lentinus giganteus , has been used as a culinary mushroom and is increasing in popularity for its medicinal properties and commercial prospects. Recently, it was reported that P. giganteus contained bioactive compounds that mimic neurite growth factor (NGF) which were accountable for neurite stimulation [10], possessed liver protection properties [11] and were a healthy dietary supplements for brain and cognitive health [12]. Hence, the aim of this study was to examine the anti-inflammatory effect of ethanol extract of P. giganteus (EPG) on LPS and combination of LPS and H 2 O 2 -induced RAW 264.7 macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we investigated further the specific role of SMS1 in neuronal cells. We used the Neuro-2a cell line that is of neuronal origin, and has been extensively used as a cell culture model to study neuronal differentiation, axonal growth, and signaling pathways [38, 39, 56, 57]. …”
Section: Discussionmentioning
confidence: 99%